Principles of Economics - Karl E Case and others; Fair Ray C; Oster Sharon M (Noida Pearson, 2022)
Reviewers tell us that case/fair/Oster is one of the all-time bestselling principles of economics texts because they trust it to be clear, thorough and complete. Readers of Principles of Economics, twelfth edition, global edition, come away with a basic understanding of how market economies function, an appreciation for the things they do well and a sense of things they do poorly. With the latest research and added exercises, students begin to learn the art and science of economic thinking and start to look at some policy and even personal decisions in a different way.FeaturesSpotlights Recent ResearchShows the power and breadth of economic modelsIntroduction of a competitive market model first, followed by non-competitive market structures gives students a clear understanding of basic economic theory and how market opportunities operate.Keynesian Cross material is integrated throughout the textIncorporation of international examples and applications includes discussion of.The many countries that contributed to creating the iPod (Chapter 1).How UPS is using technology to speed worldwide delivery (Chapter 7).How high speed trains in Europe benefit travellers, the environment and the economies of communities served (Chapter 10).The world$1 (Bs distribution of income and how technology affects distribution (Chapter 33).The world economy (Chapters 35 and 36)Table of Contents Part I. Introduction to Economics1. The Scope and method of economics2. The economic problem. Scarcity and Choice3. Demand, Supply and Market Equilibrium4. Demand and Supply Applications5. ElasticityPart II. the Market System6. Household Behaviour and Consumer Choice7. The Production Process. the Behaviour of Profit-Maximizing Firms8. Short-Run Costs and Output Decisions9. Long-Run Costs and Output Decisions10. Input Demand. the Labour and Land Markets11. Input Demand. the Capital Market and the Investment Decision12. General Equilibrium and the Efficiency of Perfect Competition Part III. Market Imperfections and the Role of Government13. Monopoly and Antitrust Policy14. Oligopoly15. Monopolistic Competition16. Externalities, Public Goods and Common Resources17. Uncertainty and Asymmetric Information18. Income Distribution and Poverty19. Public Finance. the Economics of TaxationPart IV. Concepts and Problems in Macroeconomics20. Introduction to Macroeconomics21. Measuring National Output and National Income22. Unemployment, Inflation and Long-Run GrowthPart V. The Core of Macroeconomic Theory23. Aggregate Expenditure and Equilibrium Output24. The Government and Fiscal Policy25. Money, the Federal Reserve and the Interest Rate26. The Determination of Aggregate Output, the Price Level and the Interest Rate27. Policy Effects and Cost Shocks in the AS/AD Model28. The Labour Market in the Macro economy Part VI. Further Macroeconomics Issues29. Financial Crises, Stabilization and Deficits30. Household and Firm Behaviour in the Macro economy. A Further Look31. Long-Run Growth32. Alternative Views in MacroeconomicsPart VII. the World Economy33. International Trade, Comparative Advantage and Protectionism34. Open-Economy Macroeconomics. The Balance of Payments and Exchange Rates35. Economic Growth in Developing EconomiesPart VIII. Methodology36. Critical Thinking abouts
Keywords: Market System; Macroeconomics; World Economy; Inflation